Good news about Mozambique s agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Above-average grain harvests throughout most of Mozambique have boosted household grain reserves. Food access at household levels has improved due to good harvests of maize, sorghum, millet, rice, groundnuts, beans, and cassava, as well as...